A123 NON-MELANOMA SKIN CANCER IN IBD PATIENTS TAKING 6-TGN ANTIMETABOLITES A POPULATION STUDY. (15th March 2019) - Petropolis, H; Cui, Y; Stewart, S; Heisler, C; Jones, J
Abstract: Background: Non-melanoma skin cancer (NMSC) rates have been shown to increase in Inflammatory Bowel Disease (IBD) patients taking 6-thioguanine (6-TGN) antimetabolites (Azathioprine and 6-Mercatopurine). There is limited population-based data assessing the risk of NMSC in IBD patients on 6-TGN and anti-tumor necrosis factor (anti-TNF) therapy. Aims: To determine the risk of NMSC amongst IBD patients on 6-TGN antimetabolites and anti-TNF therapies in a longitudinal, population-based Canadian cohort Methods: This was a retrospective cohort study using population-based administrative data from Saskatchewan (1970 to 2011). IBD and NMSC cases were identified through application of validated administrative definitions to ICD billing codes. Using population-based drug dispensal data IBD cases were classified as "exposed" and "unexposed" to each of 6-TGN antimetabolites and anti-TNF therapies. Univariate and multivariate conditional logistic regression and cox-proportional hazard analyses were performed. Hazard ratios were adjusted for age, sex, location, and medication. Results: A total of 8713 prevalent IBD cases were identified for inclusion, 51.6% CD and 48.4% UC. There were 349 cases of NMSC, 68 patients were exposed to 6-TGN and 281 non-exposed. The unadjusted hazard ratio (HR) was 0.74 in IBD patients exposed to 6-TGN compared to non exposed, p 0.0276 (95% CI 0.57–0.97). Stratified by age (<50 or 50 and older) the adjusted HR was 1.18 in IBD patients <50 years old, p 0.40 (0.8–1.74) and 1.38 ≥50 years old, p 0.1708 (0.87–2.20). The adjusted HR in CD patients < 50 years old was 1.08, p 0.7531 (0.67–1.73) and 1.78 ≥50 years old, p 0.030 (1.06–3.00). The adjusted HR in UC patients < 50 years old was 1.32, p 0.4232 (0.67–2.57) and 0.47 ≥50 years old, p 0.2624 (0.12 – 1.77) Conclusions: Overall, lower rates of NMSC in IBD patients taking 6-TGN compared to those not exposed to 6-TGN were observed. However when stratified for age CD patients greater than age 50 exposed to 6-TGN had statistically higher rates of NMSC compared to those not exposed, suggesting an age-related effect. Analyses to better understand the association between 6-TGN on NMSC risk which explore cumulative exposure to 6-TGN therapy and the impact of anti-TNF on NMSC will be performed. This study contributes additional data that further elucidates the relationship between 6-TGN exposure and development of NMSC Funding Agencies: